Optimization of Antibiotic Prophylaxis in Minor Gynecologic Operations - M. S. Selikhova; S. V. Vdovin; M. V. Mikhailovskaya (Антибиотики и Химиотерапия, 2020)
The aim of the study was to estimate the efficacy of various variants of antibiotic prophylaxis of infectious complications in female patients after histeroscopy. 109 patients were examined. The patients were hospitalized for planned historoscopy. 55 of them were treated prophylactically to prevent infectious complications with a broad spectrum antibiotic administered intravenously 30 min prior to the operation. A course antimicrobial therapy during the postoperative period was applied to 54 females. The results of the trial showed that single administration of an antimicrobial provided high level prevention of infectious complications, whereas the use of course antimicrobial therapy during the postoperative period was of no advantage by the efficacy.